Catalyc nexus : architecture as an interconnected resilience hub towards independence and self-efficiency in a complex socio-ecological landscape - Hugo, Jan (University of Pretoria, 2022)
Mini Dissertation (MArch Prof (Architecture))-- University of Pretoria, 2021.